ANALISIS TEKS DESKRIPSI PADA PEMBELAJARAN DALAM JARINGAN KELAS VII SMP NEGERI 23 PONTIANAK - Hariani, Nur Fitri; Heryana, Nanang; samad, Abdus (Universitas Tanjungpura, 2024)
This study examines the general problem of discussing and analyzing descriptive texts written by students in online learning. Specific problems in this study discussaspects of writing descriptive text, namely the title, structure and use of language. The research method used in this research is descriptive in the form of qualitative research. Sources of data in this study were seventh grade students of SMP Negeri23 Pontianak who wrote descriptive texts. The data collection technique used is thedocument technique. The data collection tool used is the researcher himself as the main instrument and data analyzer. Based on the results of the analysis that has been done, it can be seen that the resultsof students' assignments in writing descriptive texts on online learning are 6 students in thevery good category and 19 students in the goodcategory. The total score for the overall aspect is 334. Based on the results of the study,the suggestions for further researchers are:to addsomeassessment criteria from all aspects, such as writing correct sentences. This isbecause many errors are found in the descriptive text written by students.